Type II Diabetes mellitus: An analysis of prevention, education, and control policies (Research, Society and Development, 2025)
Type 2 Diabetes Mellitus (DM2) is one of the chronic conditions with the greatest impact on public health, influenced by factors such as sedentary lifestyle, inadequate diet, population aging, and socioeconomic inequalities. Given this scenario, the present study aimed to analyze the most effective strategies for prevention, education, and control of type 2 Diabetes Mellitus within public health policies, considering their implementation and impact on patients' quality of life. The narrative literature review showed that educational programs focused on self-care, healthy eating, and physical activity significantly reduce the incidence of DM2 and improve glycemic control. However, barriers such as low education levels, financial difficulties, and restricted access to health services compromise adherence to treatment, especially among vulnerable populations. Public policies, despite advances, still face challenges related to equity and the effectiveness of the proposed actions. The studies analyzed demonstrate that interdisciplinary clinical management, involving physicians, nutritionists, nurses, and psychologists, represents the most effective approach for disease control and prevention of complications. Conclui-se que estratégias integradas, contínuas e sensíveis às condições socioculturais são essenciais para melhorar os desfechos clínicos e reduzir o impacto do DM2 na população.